Effectiveness of a Kata Exercise Course on Static and Dynamic Balance in Hyperactive Children - Sohyela Roshan; Rezvan Souri; Mohammad Jalilvand (Islamic Azad University, Hamedan Branch, 2024)
Objective Movement and balance skills of children with attention deficit/hyperactivity disorder are weaker than normal children. The purpose of this study was to investigate the effectiveness of a course of kata exercises on static and dynamic balance in children with attention deficit/hyperactivity disorder. Methods This research was semi-experimental. The statistical population of the current study was all female children aged 10 to 12 years old with attention deficit/hyperactivity disorder in Hamadan city. The subjects of this research were 30 children who were selected by convenience sampling. At first, the characteristics of body measurements and static and dynamic balance pre-tests of children were recorded. After matching, subjects were randomly assigned to two control or experimental groups of 15 individuals. Then the participants of the experimental group participated in the protocol of kata exercises for 12 weeks and three sessions per week. After the last training session, the post-test of static and dynamic balance were measured in the same conditions as the pre-test. Independent and dependent t-tests were used to analyze the data. Results 12 weeks of kata exercises led to a significant increase in static balance with the dominant leg (P<0.001), static balance with the non-dominant leg (P<0/001) and dynamic balance in different directions (P<0.001) in children with attention deficit/hyperactivity disorder in Hamedan. Conclusion Therefore, it can be concluded that kata exercises can be a useful training method to help children with attention deficit hyperactivity disorder to improve their static and dynamic balance.